2021
DOI: 10.1158/1078-0432.ccr-21-0401
|View full text |Cite
|
Sign up to set email alerts
|

A Low Tumor Mutational Burden and PTEN Mutations Are Predictors of a Negative Response to PD-1 Blockade in MSI-H/dMMR Gastrointestinal Tumors

Abstract: Approximately half of microsatellite instability-high (MSI-H)/mismatch repair-deficient (dMMR) tumors do not respond to PD-1 blockade, indicating the importance of the identification of predictive biomarkers associated with less responsiveness to PD-1 blockade. Among 45 MSI-H/dMMR gastrointestinal (GI) tumors, a low tumor mutational burden (TMB) and PTEN mutations were mutually exclusive and were associated with poor clinical outcomes to PD-1 blockade. PTEN mutations in the phosphatase domain were associated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 37 publications
1
66
0
Order By: Relevance
“…TMB is a reliable efficacy factor for immunotherapy (11,(18)(19)(20)(21). Studies have demonstrated that those with low TMB, as seen in this case, showed less favorable survival rate (11,17,18,(20)(21)(22)(23)(24). MSI-H/ dMMR tumors are identified with high clonality of nonsynonymous mutations (also high TMB), leading to the presence of robust altered proteins, known as neoantigens (25).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…TMB is a reliable efficacy factor for immunotherapy (11,(18)(19)(20)(21). Studies have demonstrated that those with low TMB, as seen in this case, showed less favorable survival rate (11,17,18,(20)(21)(22)(23)(24). MSI-H/ dMMR tumors are identified with high clonality of nonsynonymous mutations (also high TMB), leading to the presence of robust altered proteins, known as neoantigens (25).…”
Section: Discussionmentioning
confidence: 69%
“…Optimal TMB cut-offs vary among different studies. However, levels lower than 10 Muts/Mb are generally categorized as low (1,11,17). TMB is a reliable efficacy factor for immunotherapy (11,(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 22 , 30 Recent studies have shown that activation of the PI3K pathway regulates tumor-intrinsic and immune-intrinsic features of the immunosuppressive tumor microenvironment. 53 , 54 In particular, PTEN abrogation generates an immune-suppressive microenvironment by altering cytokine secretion patterns. 8 Moreover, a few studies have indicated that activation of PI3K signaling may promote immune escape through regulating PDCD1 (PD-1)/CD274 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the binding of PD-1 and PD-L1 in the tumor microenvironment can inhibit T-cell activity and promote tumor cell evasion of immune surveillances (30). Thus, low PD-(L) 1 expression is associated with better prognosis (31,32). Because GBC was a highly aggressive malignant tumor prone to local infiltration and hematogenous metastasis at an early stage, we performed a tumor microenvironment assay on the postoperative specimen of this patient, which might reflect the tumor immune microenvironment of the patient after recurrence to some extent.…”
Section: Discussionmentioning
confidence: 99%